The combined exercise stress echocardiography and cardiopulmonary exercise test for identification of masked heart failure with preserved ejection fraction in patients with hypertension. (January 2016) - Nedeljkovic, Ivana; Banovic, Marko; Stepanovic, Jelena; Giga, Vojislav; Djordjevic-Dikic, Ana; Trifunovic, Danijela; Nedeljkovic, Milan; Petrovic, Milan; Dobric, Milan; Dikic, Nenad; Zlatar, Milan; Beleslin, Branko
Background: Heart failure with preserved ejection fraction (HFpEF) is commonly associated with hypertension (HTN). However, resting echocardiography (ECHO) can underestimate the severity of disease. Exercise stress echocardiography (ESE) and the cardiopulmonary exercise testing (CPX) appeared to be useful tests in dynamic assessment of HFpEF. The value of combined exercise stress echocardiography cardiopulmonary testing (ESE-CPX) in the identification of masked HFpEF is still undetermined. Objective: The purpose of this study was to analyse the value of the combined ESE-CPX in the identification of masked HFpEF in patients with HTN, dyspnoea and normal resting left ventricular (LV) systolic and diastolic function. Methodology: We studied 87 patients with HTN, exertional dyspnoea and normal resting LV function. They all underwent ESE-CPX testing (supine bicycle, ramp protocol, 15 W/min). ECHO measurements were performed at rest, and at peak load. Achievement of peak E/e' ratio>15 was a marker for masked HFpEF. Results: Increase of E/e'>15 occurred in 8/87 patients (9.2%) during ESE-CPX. Those patients had the lower peak VO2 ( p  = 0.012), the lower VO2 at anaerobic threshold ( p  = 0.025), the lower workload ( p  = 0.026), the lower peak partial pressure end tidal carbon dioxide (PetCO2) ( p  < 0.0001), and the higher VE/VCO2 slope ( p  < 0.0001) which was an independent multivariate predictor of HFpEF ( p  = 0.021), with the cut-off value of 32.95 according to the receiver-operator characteristic (ROC) curve (sensitivity (Sn) 100%, specificity (Sp) 90%). Conclusion: The combined ESE-CPX test is feasible and reliable test that can unmask HFpEF and may become an important aid in the early diagnosis of HFpEF, excluding the other causes of exertional dyspnoea.